Évolution récente de l’île d’Orléans - Mingasson, Christian (Cahiers de géographie du Québec, 1956)
This is an abridged form of a thesis presented on the recent evolution of Orleans island, near Québec.It is mainly a study of its dominant economic activity : its agricultural production and its agrarian System. The other economic activities such as ship-building and tourism are also examined.In a second section, the author deals with the demography, settlement and social structure of the population.